La question du rythme : entre une tradition (Maksymilian Kawczyński) et une modernité (Henri Meschonnic) - Rapak, Wacław (2023)
My point in the present article is to come back once again to the question that seems to me fundamental both for the theoretical reflection and for the interpretative practice of literary discourses. This is certainly the case in my studies and articles. As the title of my article announces, in the present article I intend to discuss the confrontation between a traditional approach, proposed at the end of the nineteenth century by Maksymilian Kawczyński, and the modern approach of Henri Meschonnic's theory of the rhythm-sense-subject.
Keywords: rhythm; theory; discourse; literature